Umbilical cord blood transplantation after nonmyeloablative conditioning: impact on transplantation outcomes in 110 adults with hematologic disease - Brunstein, Claudio G. (American Society of Hematology, 2007)
We evaluated the efficacy of umbilical cord blood (UCB) in the setting of a nonmyeloablative regimen consisting of fludarabine (200 mg/m(2)), cyclophosphamide (50 mg/kg), and a single fraction of total body irradiation (200 cGy) with cyclosporine and mycophenolate mofetil for posttransplantation immunoprophylaxis. The target cell dose for the UCB graft was 3.0 × 10(7) nucleated cells/kg, resulting in the selection of a second partially human leukocyte antigen-matched UCB unit in 85%. One hundred ten patients with hematologic disease were enrolled. Neutrophil recovery was achieved in 92% at a median of 12 days. Incidences of grades III and IV acute and chronic graft-versus-host disease (GVHD) were 22% and 23%, respectively. Transplantation-related mortality was 26% at 3 years. Survival and event-free survival (EFS) at 3 years were 45% and 38%, respectively. Favorable risk factors for survival were absence of high-risk clinical features (Karnofsky 50-60, serious organ dysfunction, recent fungal infection, P < .01) and absence of severe GVHD (P = .04), and favorable risk factors for EFS were absence of high-risk clinical features (P < .01) and use of 2 UCB units (P = .07). These findings support the use of UCB after a nonmyeloablative conditioning as a strategy for extending the availability of transplantation therapy, particularly for older patients.